Implementation of a Thematic Analysis Method to Develop a Qualitative Model on the Authentic Foreign Language Learning Perspective: A Case Study in the University of Northern Cyprus - Mortazavi, Mohsen; Davarpanah, Afshin (Mdpi, 2021)
Environmentally friendly occasions allow foreign language learners to further concentrate on realizing their extensive knowledge of the English language. Exercises and activities performed in foreign language classes have been criticized for a lack of authenticity, which prevents language learners from learning the real-life usage of language. In this paper, we developed a qualitative model based on the thematic analysis method (TAM) to distinguish the efficacy of research strategies. The number of participants was defined based on theoretical saturation. To collect the data, 18 participants were selected from the Eastern Mediterranean University (EMU) in Cyprus. The selection of participants was according to their involvement in research-based projects. Theoretical saturation occurred after 15 semi-structured interview forms from participants; however, we selected three extra participants to obtain more reliable results. The reliability of the qualitative model was explicitly illustrated by colleagues who were experts in this field by reviewing and analyzing the proposed model with previous models. It was concluded that the two principles of motivation (principle 11) and provision of collaborative opportunities (principle 4) had the highest frequencies, of 22.47% and 19.66%.
Keywords: foreign language learning; e-learning; authentic environment; principles; English